IMPLEMENTASI METODE RESEARCH AND DEVELOPMENT (R & D) PADA APLIKASI PENGELOLAAN ARSIP - Muh. Farid Wajdi; Mika Tandililing (P3M STMIK Profesional Makassar, 2022)
Archives are one of the important assets owned by the regional revenue agency office so that more attention is needed so that it can facilitate the process of processing archives to be efficient and easy. This study aims to design a web-based application of the archives of the regional revenue agency using the R&D method and interviews, observations, literature studies as data collection techniques so that the results of this study are expected to help the work in the office of the regional revenue agency in South Sulawesi.